META-ANALYSIS: THE IMPACT OF BCG IMMUNIZATION, CONTACT HISTORY AND PARENTAL KNOWLEDGE ON CHILDHOOD PULMONARY TB: Meta-Analisis: Pengaruh Imunisasi BCG, Riwayat Kontak dan Pengetahuan Orang Tua Terhadap TBC Paru pada Anak - Kalsum, Ummi; Paradiba, Anggia; Butar Butar, Marta; Nugraha, Fathan Iman (Jurnal Berkala Epidemiologi, 2026)
Background: The problem of childhood pulmonary TB is still high worldwide and in Indonesia. Several studies have found various risk factors that contribute to the incidence of pulmonary TB in children. Purpose: To analyze the results of research related to BCG immunization, contact history, and parental knowledge with the incidence of childhood pulmonary TB. Methods: The study design was a systematic review with meta-analysis. Journal sources from 3 databases, namely Google Scholar, Pubmed, and Scopus using Publish or Perish Software with keywords using boolean operators. The inclusion criteria were full text from 2019 to 2023, articles in Indonesian or English, observational studies, the population was children, using multiple logistic regression multivariate analysis with adjusted odds ratio. Ten articles qualified for inclusion out of 11,471 identified. Data analysis using RevMan 5.4. Results: The pooled proportion of childhood pulmonary TB from four primary studies was 16.35% (95%CI: 4.34-24.52). Contact history (SMD=9.52; 95% CI=3.61-25.09; p-value=0.05) was statistically significant”while BCG immunization and parental knowledge were not significant. No publication bias was detected. Conclusion: A history of contract increases the risk of pulmonary TB in children. It is recommended that parents prevent their children from contact with TB sufferers through implementation of appropriate health protocols to reduce the risk of TB transmission.